Progress in Mathematical Ecology - Sergei Petrovskii (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Mathematical ecology is an area of applied mathematics concerned with the application of mathematical concepts, tools and techniques, usually in the form of mathematical models, to problems arising in population dynamics, ecology and evolution. This Special Issue is designed to provide a snapshot of the state of the art in mathematical ecology. Topics of interest are (in no particular order) biological invasions, biological control, ecological pattern formation, ecologically relevant multiscale models, food webs, individual movement and dispersal, eco-epidemiology, evolutionary ecology, agroecosystems, regime shifts and early warning signals, synchronization and chaos. The list is inclusive rather than exclusive, and a few other relevant topics will also be considered.